WAYS OF TEACHING A FOREIGN LANGUAGE TO STUDENTS AT DIFFERENT LEVELS - Odilov Nozimbek (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  offers  illustrations  and  instances  highlighting  the significance of acquiring English language skills. It also delivers a concise summary of  the  challenges  associated  with  learning  English  in  teenagers  and  grown-ups. Additionally, it includes details about three successful approaches to mastering the English language.